2011 3rd International Conference on Electronics Computer Technology 2011
DOI: 10.1109/icectech.2011.5941953
|View full text |Cite
|
Sign up to set email alerts
|

Design and reduction of wattage losses in solar module using AR coating, cell-to-cell gap and thickness

Abstract: Th is the Solar energy. A Pho photons of li medium of co effect. A pho sunlight into e efficiency limi with conventi about 24.7% efficiency is d resistive loss, reduce the effi the different m and technique Keywords Photovoltaic de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…Kumar vd. [17] bakır şeridin kalınlığının arttırılmasının ve hücreden hücreye boşluğun azaltılmasının direnç güç kaybını azaltmaya yardımcı olabileceğini göstermiştir.…”
Section: Rc(kesik) = Nrc(tam)unclassified
See 1 more Smart Citation
“…Kumar vd. [17] bakır şeridin kalınlığının arttırılmasının ve hücreden hücreye boşluğun azaltılmasının direnç güç kaybını azaltmaya yardımcı olabileceğini göstermiştir.…”
Section: Rc(kesik) = Nrc(tam)unclassified
“…Öte yandan, modüllerin yansıma önleyici katmanlarının optimize edilmesi, bir arka levha reflektörü kullanılarak çıkış gücünün iyileştirilmesi gibi optik kayıpların olumsuz etkilerinin minimize edilmesi amacıyla çalışmalar yapılmıştır [17,18].…”
Section: Rc(kesik) = Nrc(tam)unclassified
“…Some investigations were already done in order to reduce the optical losses. For example, Kumar et al [3] provided a method to optimise antireflective coatings of PV modules. In a publication by Su et al [4], improving the output power by using a back sheet reflector was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Caballero et al [6] performed series resistance modelling of PV modules to optimise the front metal grid structure. Kumar et al [3] showed that increasing the thickness of the copper ribbon and reducing the cell-to-cell gap could help reduce resistive power loss.…”
Section: Introductionmentioning
confidence: 99%